Thinking Analogy in Solving Indirect Analogy Problems based on Information Processing Theory - Kristayulita, Kristayulita; Sucipto, Lalu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Cognitive ability in solving analogy problems really needs the right information processing. The core cognitive process in analogy thinking occurs when students make a mapping between the target problem and the source problem. This research aims to describe analogical thinking in solving indirect analogy problems based on information processing theory. The method usesd in this research is qualitative descriptive. The subject in this study were third and fifth-semester students of the Mathematics Tadris Program FTK UIN Mataram. Instruments are source problems and target problems use indefinite integral problems in the Integral Calculus course. Data analysis is used by using triangulation of methods and data sources. The results showed that there were 51.06% able to solve the target problem where students are able to recall long-term memory information related to solving source problems that have similarities to solving target problems. Source problem-solving information taken from long-term memory is used by students in solving target problems in short-term memory. The processing of information in short-term memory depends on the mapping process with previous information in long-term memory. Therefore, as a mathematics teacher, he is able to emphasize certain materials which are initial knowledge to study further material.